Three distinct reactions of 3,4-dihydroisoquinolines with azlactones: Novel synthesis of imidazoloisoquinolin-3-ones, benzo[a]quinolizin-4-ones, and benzo[d]azocin-4-ones - Rattana Worayuthakarn (2018)
(Diagram presented) A facile and direct synthetic entry to tricyclic imidazoloisoquinolin-3-ones and benzo[a]quinolizin-4-ones is reported based on the ring annulation of 1-unsubstituted and 1-substituted dihydroisoquinolines with azlactones under neutral conditions in a one-step procedure. Bicyclic 2,3-dihydrobenzo[djazocin-4-ones were also prepared using simple azlactone and 1-substituted dihydroisoquinolines in a one-pot reaction. © 2006 American Chemical Society.